Evaluation of Clinical and Hematological Inflammatory Profile in Patients Treated for Oral Squamous Cell Carcinoma - A Prospective Cohort Study - G Chenchulakshmi; Arvind Muthukrishnan; Ravleen Nagi (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Cancer treatment can lead to significant morbidities that may persist throughout the life of a patient. Over the past 30 years, there has been no improvement in the percentages of morbidity and mortality of oral squamous cell carcinoma (OSCC) despite advances in therapeutic approaches. Objective: To evaluate the role of hematological parameters as prognostic inflammatory indicators in patients treated for OSCC. The objective was to assess pre- and post-treatment neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) in patients with OSCC. Methods: The methodology in this study was to draw 2 mL of blood samples from patients with OSCC, both pre-treatment and post-treatment, at regular intervals of 2 months up to 12 months. Results: There was no statistically significant difference observed in NLR and PLR when comparing the NLR and PLR baseline with other months (2nd, 4th, 6th, 8th, 10th, and 12th months); however, there was a statistically significant difference between the LMR baseline and other months. At the end of the 12th month, NLR was high in 13 (25%) patients, PLR was low in 15 (30%) patients, and LMR was normal in 25 (50%) patients in comparison with the standard values. Conclusion: Hematological parameters have the potential to serve as prognostic inflammatory indicators in patients with OSCC.